Multitasked closed-loop control in anesthesia. - Gentilini, A.
Automatic controllers capable of regulating multiple patient outputs for higher-quality anesthesia treatment are described. The first steps toward the development of an autonomous anesthesia system at the authors' laboratory are presented. The controllers are implemented on a real-time platform and tested on humans to quantify the benefits that may result from their use in routine practice. To date, the staff at the University Hospital in Bern can rely on controllers that regulate six different patient outputs. Overall, more than 150 patients were treated with closed-loop controllers during general anesthesia. These controllers regulate O/sub 2/, CO/sub 2/, and inspired and expired anesthetic gas concentrations in the breathing system, as well as mean arterial pressure and depth of hypnosis through bispectral index.
Keywords: Bern; CO/sub 2.; O/sub 2.; University Hospital; Anesthesia; Bispectral index; Breathing system; Expired anesthetic gas concentrations; Hypnosis depth; Inspired anesthetic gas concentrations; Multitasked closed-loop control